Small-scale irrigation for arid zones - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Small-scale irrigation for arid zones - principles and options by Daniel Hillel 1997 56pp ISBN 92 5 103896 1